Burden of malaria is higher among children in an internal displacement camp compared to a neighbouring village in the Democratic Republic of the Congo. (December 2016) - Charchuk, Rhianna; Paul, Makelele; Claude, Kasereka; Houston, Stan; Hawkes, Michael
Abstract Background In the Democratic Republic of the Congo (DRC), violent conflict has caused the displacement of millions of people into camps where they are exposed to poor living conditions and high rates of infectious diseases. Malaria, in particular, is a major cause of mortality in children under five; however, the burden of disease in displacement camps has not previously been described. Methods Two cross-sectional surveys were performed. First, prevalence ofPlasmodium falciparum antigenemia was measured in a random sample of 200 children living in a displacement camp and 200 children from a nearby village (control group). Second, the proportion of febrile illness attributable to malaria was measured in a study of 100 children from the displacement camp and 100 children from the control village presenting to the same health clinic with fever. All participants were tested forP. falciparum with a rapid diagnostic test and additional demographic data, clinical characteristics, and malaria risk factors were determined using a parental questionnaire. Results In the community survey, children living in the displacement camp had a higher prevalence ofP. falciparum infection (17 %) than controls (7.5 %) (OR 2.6; 95 % CI 1.3–4.1; P = 0.0095). In the clinic-based survey, the proportion of febrile illness attributable to malaria was higher among children from the displacement camp (78 %) than controls (39 %) (OR 5.5; 95 % CI 3.0–10.3; P < 0.001). Household bed net ownership and use was significantly lower in the displacement camp than control village in both surveys. Statistically significant differences in household wealth, maternal education, and exposure to community violence were also found. Conclusions Population displacement due to violent conflict appears to be a risk factor for malaria, a major cause of child mortality. Children living in displacement camps are a relatively understudied population, but have a high burden of malaria, despite control programmes focused on bed net distribution.